Hambatan-hambatan dalam Berkomunikasi Internasional Mahasiswa Pengembangan Masyarakat Islam Kelas B UIN Sumatera Utara - Winda Kustiawan; Intan Suci Melani; Rawiyah Safitri Amanda; Vera Widya Ningsih Rangkuti; Dinny Rahmayani Zebua (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Barriers to communication in the Islamic Community Development department actually stem from sending messages and receiving messages as well as how each individual in it responds to messages conveyed during one and a half year lectures conducted online. The obstacles that occur are also due to the lack of confidence from some students with several groups that seem to have interaction and strength in the class. Interpersonal communication that does not go well causes many obstacles that arise in the class. It can be from between Kosma and its members or between fellow members. Communication that is built without interest and no direct interaction can eliminate the main factor in interpersonal communication. Emotions that should be well formed and built when face to face actually become the main problem in the Islamic Community Development class B class. Based on the results of the study, there are three obstacles that occur in the class, namely mechanical, semantic and human barriers. These three obstacles become disturbances that arise among fellow students in the Stambuk 2020 Islamic Community Development class